Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the inverse of the function [tex]\( f(x) = 5x \)[/tex], we need to follow these steps:
1. Definition of the Function:
We start with the given function [tex]\( f(x) = 5x \)[/tex].
2. Rewrite using [tex]\( y \)[/tex]:
To find the inverse function, we'll rewrite [tex]\( f(x) \)[/tex] as [tex]\( y \)[/tex]:
[tex]\[ y = 5x \][/tex]
3. Solve for [tex]\( x \)[/tex]:
We need to solve this equation for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 5x \][/tex]
Divide both sides of the equation by 5 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{y}{5} \][/tex]
4. Express the Inverse Function:
Since [tex]\( x = \frac{y}{5} \)[/tex], we can write the inverse function [tex]\( f^{-1}(x) \)[/tex]. To match the notation, replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] in our final expression:
[tex]\[ f^{-1}(x) = \frac{x}{5} \][/tex]
5. Select the Correct Option:
Among the given options:
- [tex]\( f^{-1}(x) = -5x \)[/tex]
- [tex]\( f^{-1}(\pi) = -\frac{1}{5} x \)[/tex]
- [tex]\( f^{-1}(x) = \frac{1}{5} x \)[/tex]
- [tex]\( f^{-1}(x) = 5x \)[/tex]
The correct option is:
[tex]\[ f^{-1}(x) = \frac{1}{5} x \][/tex]
Therefore, the correct answer is the third option:
[tex]\[ f^{-1}(x) = \frac{1}{5} x \][/tex]
1. Definition of the Function:
We start with the given function [tex]\( f(x) = 5x \)[/tex].
2. Rewrite using [tex]\( y \)[/tex]:
To find the inverse function, we'll rewrite [tex]\( f(x) \)[/tex] as [tex]\( y \)[/tex]:
[tex]\[ y = 5x \][/tex]
3. Solve for [tex]\( x \)[/tex]:
We need to solve this equation for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 5x \][/tex]
Divide both sides of the equation by 5 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{y}{5} \][/tex]
4. Express the Inverse Function:
Since [tex]\( x = \frac{y}{5} \)[/tex], we can write the inverse function [tex]\( f^{-1}(x) \)[/tex]. To match the notation, replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] in our final expression:
[tex]\[ f^{-1}(x) = \frac{x}{5} \][/tex]
5. Select the Correct Option:
Among the given options:
- [tex]\( f^{-1}(x) = -5x \)[/tex]
- [tex]\( f^{-1}(\pi) = -\frac{1}{5} x \)[/tex]
- [tex]\( f^{-1}(x) = \frac{1}{5} x \)[/tex]
- [tex]\( f^{-1}(x) = 5x \)[/tex]
The correct option is:
[tex]\[ f^{-1}(x) = \frac{1}{5} x \][/tex]
Therefore, the correct answer is the third option:
[tex]\[ f^{-1}(x) = \frac{1}{5} x \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.